THE IMPLEMENTATION OF E-GOVERNMENT THROUGH THE VILLAGE FINANCIAL SYSTEM APPLICATION (SISKEUDES) IN PAGERWOJO VILLAGE, BUDURAN SIDOARJO - Agustin, Febby Dwi; Mursyidah , Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Village Financial System Application (SISKEUDES) as a form of E-Government in improving financial management in Pagerwojo Village, Buduran District, Sidoarjo Regency. Method: The research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. Results: The findings show that the implementation of SISKEUDES has enhanced efficiency, accountability, and transparency in village financial management. Prior to its adoption, financial reporting was conducted manually, which often led to errors and delays, whereas with SISKEUDES, financial processes became more structured and aligned with regulatory standards. Nevertheless, challenges persist, including limited human resources, inadequate internet infrastructure, and suboptimal transparency toward the community. Moreover, based on Indrajit’s (2005) six components of E-Government, the aspect of Citizen Interaction remains weak, as the village lacks a dedicated digital platform such as a website or community service application. Novelty: This study contributes by providing an evaluative perspective on SISKEUDES not only as a financial management tool but also as a catalyst for strengthening governance, emphasizing the need for capacity building and digital infrastructure development to ensure sustainability and inclusivity in village-level E-Government practices.